Dictionary of scientific biography. [Volumes 1 & 2] - Gillispie, Charles Coulston; American Council of Learned Societies (New York : Charles Scribner's Sons, 1981)
Contains articles that provide information about the professional lives of scientists, from classical antiquity to modern times, who have made significant contributions to the fields of mathematics, astronomy, physics, chemistry, biology, and earth science. Arranged alphabetically from Abailard to Buys Ballot.
v. 1. Pierre Abailard-L.S. Berg -- v. 2. Hans Berger-Christoph Buys Ballot.
"Published under the auspices of the American Council of Learned Societies"--P. facing t.p.
Includes bibliographical references.
Wilson's Senior High School.
Young Adult
Keywords: Scientists -- Biography -- Dictionaries; Scientists -- Biography -- Dictionaries